2020
DOI: 10.1021/acs.jchemed.0c01116
|View full text |Cite
|
Sign up to set email alerts
|

CheMakers: Playing a Collaborative Board Game to Understand Organic Chemistry

Abstract: Organic chemistry is often considered by undergraduate students to be the most difficult branch of chemistry. Instructors and senior students collaborated to develop CheMakers, a board game to help students understand organic reaction mechanisms and implement mechanistic thinking. The game, played by 3 teams, was designed to invoke meaningful discussions among students. To win the game, the students need to work together as a team to prepare their strategies, solve organic chemistry problems, and reach their o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 32 publications
0
21
1
Order By: Relevance
“…(2015) denoted that students get motivated while learning chemistry through games. While the study findings and those of previous studies (e.g., Battersby et al., 2020 ; Franco-Mariscal et al., 2016 ; Sousa Lima et al., 2019 ) suggest that game-based learning is bound to improve students' confidence in the subject matter, Zhang et al. (2021) cautioned that there was not enough evidence that the game could improve students' interest in learning chemistry.…”
Section: Study Implicationscontrasting
confidence: 58%
See 1 more Smart Citation
“…(2015) denoted that students get motivated while learning chemistry through games. While the study findings and those of previous studies (e.g., Battersby et al., 2020 ; Franco-Mariscal et al., 2016 ; Sousa Lima et al., 2019 ) suggest that game-based learning is bound to improve students' confidence in the subject matter, Zhang et al. (2021) cautioned that there was not enough evidence that the game could improve students' interest in learning chemistry.…”
Section: Study Implicationscontrasting
confidence: 58%
“…This game involved 47 first-year students in an organic chemistry course. Implementers of this game ( Zhang et al., 2021 ) found that forty-three (43) of these students gave positive feedback on the possibility of playing the game again. Besides promoting higher-order thinking, creativity, and problem-solving skills, CheMakers improved students' confidence in handling difficult questions.…”
Section: Discussionmentioning
confidence: 99%
“…Organic chemistry is a subject taught in the first-year undergraduate chemistry course (CM1121) at the National University of Singapore (NUS), yet many students often regard it as one of the most difficult branches of chemistry . Since 2012, CM1121 adopted a flipped classroom teaching approach .…”
Section: How Teaching Modes Have Evolved Since the Pandemicmentioning
confidence: 99%
“…Gamification in education and training has been a topic of interest in recent years, both within and beyond academia . Within the academic setting, educational quizzes in the style of popular television game shows and even board games have been employed as didactic games to motivate students and increase their interest level with regards to learning Chemistry. Trialled and tested in several high schools, these didactic games garnered positive feedback from students who played the games. Beyond academia, a team from Brazil reported on the increased interest by companies to use gamified approaches to engage their employees in training programs …”
Section: Introductionmentioning
confidence: 99%